2017
DOI: 10.1111/joa.12613
|View full text |Cite
|
Sign up to set email alerts
|

Variation in brain anatomy in frogs and its possible bearing on their locomotor ecology

Abstract: Despite the long-standing interest in the evolution of the brain, relatively little is known about variation in brain anatomy in frogs. Yet, frogs are ecologically diverse and, as such, variation in brain anatomy linked to differences in lifestyle or locomotor behavior can be expected. Here we present a comparative morphological study focusing on the macro- and micro-anatomy of the six regions of the brain and its choroid plexus: the olfactory bulbs, the telencephalon, the diencephalon, the mesencephalon, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
1
14
1
Order By: Relevance
“…We presumed a close relationship between head compensatory movements and the type of habitat and/or locomotion. A large body of empirical work shows that the habitat and locomotion type is closely linked to morphology and/or performance (Jorgensen and Reilly, 2013;Gomes et al, 2009;Manzano et al, 2017;Moen et al, 2013;Robovská-Havelková et al, 2014;Knight, 2018;Hill et al, 2018). However, our results did not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…We presumed a close relationship between head compensatory movements and the type of habitat and/or locomotion. A large body of empirical work shows that the habitat and locomotion type is closely linked to morphology and/or performance (Jorgensen and Reilly, 2013;Gomes et al, 2009;Manzano et al, 2017;Moen et al, 2013;Robovská-Havelková et al, 2014;Knight, 2018;Hill et al, 2018). However, our results did not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 83%
“…Several anatomical (diplasiocoelous vertebrae, organization of pectoral and pelvic girdle) and behavioral (tongueprotraction mechanism) characteristics were examined but are shared with other groups of frogs. A previous study on the brain morphology of frogs revealed the relationship between locomotion/ ecology and size of the cerebellum and diencephalon (Manzano et al, 2017). Thus, a comparative neuroanatomical survey examining the endorgans and associated innervation of the inner ear responsible for compensatory movements can be promising for rationale of the uncovered pattern.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This categorization (Table ) follows Grizante, Navas, Garland, and Kohlsdorf () and Soliz et al (), who also searched for a way to incorporate more subtlety in the ecological settings of the taxa studied. For example, landing behaviour of Scinax fuscovarius is recorded as hand hit and digit hit following descriptions of movements implied in jumping (Manzano, Herrel, Fabre, & Abdala, ) (Figure ). Our field observations indicate that, occasionally, this species also exhibits belly hit.…”
Section: Methodsmentioning
confidence: 99%
“…Values of each category were inferred considering the recorded frequency of each behaviour. Likewise, climber‐walker species, as Phyllomedusa sauvagii , walk across narrow substrates using their arms, they use their digits to grip the branches while climbing, but they are also able to jump in order to escape predators and in that case, they land with their body (Manzano et al, ). Thus, we assigned them 0.6 for digit hit and 0.4 for belly hit.…”
Section: Methodsmentioning
confidence: 99%